Analysis of Design Solutions in the Objects of Gravel Roads Paving Programme in Terms of Traffic Safety - Vilimas Gintalas; Daiva Žilionienė; Mindaugas Dimaitis; Darius Lukošaitis; Kristina Lipnevičiūtė; Jūratė Vitkienė (The Baltic Journal of Road and Bridge Engineering, 2008)
Recently, the accident rate in Lithuania has been among the highest ones in Europe. The experience of implementing Gravel Roads Paving Programme (Programme) shows that accident rates have been increasing on the reconstructed road sections. This enables to make an assumption that design solutions taken on the reconstructed gravel roads may be not suitable in terms of traffic safety, since, currently, attempts are made to design the mini possible deviation of the project road axis from the existing road axis. The article evaluates the quality of design solutions in terms of traffic safety in the objects of Programme through the use of the design method applied in West European countries, which is based on safety criteria and enables to evaluate traffic safety not only on the existing but on the designed two-lane suburbian roads, i.e. the level of traffic safety is determined in the design stage. The article investigates the road plan solutions in the objects of Programme. Dangerous road sections on the reconstructed or being reconstructed sections were identified, and the analysis of the real or the predictable accident rates on these sections was carried out.